PENGOMPOSAN SLUDGE HASIL PENGOLAHAN LIMBAH CAIR PT. INDOFOOD CBP DENGAN PENAMBAHAN LUMPUR AKTIF DAN EM4 DENGAN VARIASI KULIT BAWANG DAN BAWANG GORENG - Niken Wijayanti; Winardi Dwi Nugraha; Syafrudin Syafrudin (Jurnal Teknik Lingkungan, 2013)
This research in order to overcome the problems experienced PT.Indofood CBP waste by composting. The purpose of this study to determine the composition of the compost material so that the optimal amount of waste that can be reused as compost material can be determined. Composting process using two activators, namely Effective Microorganism 4 (EM4) and activated sludge. Mature compost meet the requirements of SNI 19-7030-2004. The best results were obtained in variations 5 using EM4 activator with a ratio of sludge: onion skins: fried onion = 8:2:1 with results C-organic 22.44%, 1.50% N-total, P-total 0.52 %, K-total of 1.08% and the ratio of C / N 14.92. In activated sludge activator with a variation of the same C-organic shows the results of 19.64%, 1.29% N-total, P-total of 0.39%, K-total 0.52% and the ratio of C / N 15.27.